2021
DOI: 10.1021/acs.jpclett.1c03094
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Homoepitaxial Junction of Organic Semiconductors: A Structurally Seamless but Electronically Abrupt Interface between Rubrene and Bis(trifluoromethyl)dimethylrubrene

Abstract: Single-crystalline organic semiconductors exhibiting band transport have opened new possibilities for the utilization of efficient charge carrier conduction in organic electronic devices. The epitaxial growth of molecular materials is a promising route for the realization of wellcrystallized organic semiconductor p−n junctions for optoelectronic applications enhanced by the improved charge carrier mobility. In this study, the formation of a high-quality crystalline interface upon "quasi-homoepitaxial" growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…As an OSC, rubrene shows temperature-dependent behaviours in different aspects. 26,58,66 Explorations of the Hall effects in the field-induced accumulation layer of single-crystal rubrene showed that the Hall mobility increased with decreasing the temperature in both the intrinsic and trap-dominated conduction regimes. 26 By photoirradiation of a rubrene single-crystal in the infrared region, the temperature dependence of the This journal is © Owner Societies 2023 decay dynamics of polarons revealed that the polaron mobility increased with decreasing the temperature, indicating a bandlike transport of large polarons.…”
Section: Resultsmentioning
confidence: 99%
“…As an OSC, rubrene shows temperature-dependent behaviours in different aspects. 26,58,66 Explorations of the Hall effects in the field-induced accumulation layer of single-crystal rubrene showed that the Hall mobility increased with decreasing the temperature in both the intrinsic and trap-dominated conduction regimes. 26 By photoirradiation of a rubrene single-crystal in the infrared region, the temperature dependence of the This journal is © Owner Societies 2023 decay dynamics of polarons revealed that the polaron mobility increased with decreasing the temperature, indicating a bandlike transport of large polarons.…”
Section: Resultsmentioning
confidence: 99%
“…Distances to the first and second slits from the sample were about 480 mm and 940 mm, respectively. The angular resolution for this double-slit setup at BL19B2 was estimated to be around 0.01° [ 38 ] when the widths of the first and second slits were set at 0.2 and 0.4 mm, respectively, whereas it was broadened to be 0.04° by opening the double-slit width to 0.5 mm [ 39 ]. In contrast, the insertion of a Ge(111) analyzer crystal made the angular resolution as fine as 0.003° enabling the HR-GIXD measurements at an undulator beamline BL46XU [ 40 ].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In this context, di(trifluoromethyl)dimethylrubrene (fmRub, Figure 13 a), a derivative of rubrene, may be a promising molecule for a combination with (unsubstituted) rubrene because these two species have distinct frontier level energies with each other [ 111 ] but are sharing very close lattice constants in their “high-mobility” molecular planes ( Figure 13 b,c) [ 112 ]. In fact, fmRub formed a “quasi-homoepitaxial” interface on RubSC with an in-plane mean crystallite size several times greater than those for conventional heteroepitaxial molecular interfaces [ 39 ].…”
Section: Epitaxy In Various Types Onto Rubrene Single Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In homoepitaxy, the growth layers are made up of the same material as the substrate, while in heteroepitaxy, the growth layers are of a different material than that of the substrate, and a distinct crystallographic relationship exists between the orientations of the substrates and the growth layers. For the epitaxial layer in the presence of a lattice mismatch between the growth layer and the substrate, a lattice mismatch ratio is commonly defined as the relative difference between the in-plane lattice constants of the growth layer and substrate. The small lattice mismatch ratio means that the lattice points of the growth layer and the substrate are in good agreement. Some studies have estimated the lattice mismatch ratio of crystalline devices having electric and optical properties using various microscopic observation techniques in the vapor epitaxial growth process. …”
Section: Introductionmentioning
confidence: 99%